Exploring the effects of alcohol use on antiretroviral therapy adherence amongst antiretroviral patients at Khotsong, a rural clinic in Lesotho - Motlomelo, Masetsibi (My University, 2019)
Introduction The Antiretroviral Therapy (ART) has a positive influence on longevity in patients with HIV, extensively reducing morbidity and mortality. However, the success of anti-retroviral therapy (ART) depends on access to treatment, being some of the challenges facing people on ART. A number of factors infuencing anti-retroviral therapy, including alcohol have been reported. The aim of the study was to explore the factors that influence antiretroviral therapy amongst ART patients at the Khotsong, a rural clinic in Lesotho. Method This study was premised on the principles of the qualitative research, coupled with an exploratory research design. For the purpose of the study, a purposive sampling technique was used to select the study participants. As such, adopting an interview guide, in-depth interviews were conducted involving twelve ART patients in 2015-2016. Results The findings of the study show several factors influencing the ART, including significant alcohol consumption, motives for alcohol use, food insecurity meant for easing medication, forgetfulness, late arrival at home and deliberate avoidance of medication amongst the patients. Conclusion The findings of the study show alcohol consumption amongst ART patients, the habit which tends to affect ART adherence. Even though alcohol consumption is noted amongst the patients, decrease in quantity and frequency of consumption is observed once the patients enroll for ART, thus indicating the effectiveness of information provided. Therefore, there is a need for improved treatment literacy and integration of alcoholfocused interventions geared towards ART patients
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the Degree of Master of Public Health. April 2019